2022
DOI: 10.3390/foods11193107
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Optimized Fermentation Conditions of SCOBY-Based Membranes and Milk Kefir Grains to Promote Various Functional Properties

Abstract: Kombucha culture (named SCOBY-Symbiotic Culture of Bacteria and Yeasts) and milk kefir grains represent multiple consortia of wild microorganisms that include lactic acid bacteria, acetic acid bacteria and yeasts with valuable functional properties. Their fermentative potential provides a wide range of derivate metabiotics (prebiotics, probiotics, postbiotics and paraprobiotics) with valuable in vitro and in vivo benefits. This study targeted the evaluation of the functionality of a co-culture of SCOBY-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Previously, in an FP obtained by co-fermentation with milk kefir grains and SCOBY, some organic acids such as lactic acid, acetic acid, citric acid, isovaleric acid, and butyric acid, which presented the following concentrations, respectively, of 24.39 mg/mL, 25.21 mg/mL, 5.77 mg/mL, 4.36 mg/mL, and 67.33 mg/mL, were synthesised by the artisanal cultures [ 12 ]. Therefore, the lactic and citric acids were not identified in the optimised fermented product’s composition obtained by fermentation of the formulated medium with a multiple starter culture, based on WKG and SCOBY microbiota; the result can be attributed to the synergistic functionality of the consortia in tested conditions, in correlation with the chemical composition of the fermentation substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in an FP obtained by co-fermentation with milk kefir grains and SCOBY, some organic acids such as lactic acid, acetic acid, citric acid, isovaleric acid, and butyric acid, which presented the following concentrations, respectively, of 24.39 mg/mL, 25.21 mg/mL, 5.77 mg/mL, 4.36 mg/mL, and 67.33 mg/mL, were synthesised by the artisanal cultures [ 12 ]. Therefore, the lactic and citric acids were not identified in the optimised fermented product’s composition obtained by fermentation of the formulated medium with a multiple starter culture, based on WKG and SCOBY microbiota; the result can be attributed to the synergistic functionality of the consortia in tested conditions, in correlation with the chemical composition of the fermentation substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture was incubated for 10 days at room temperature (22 ± 2 °C). Then, 20% ( w / w ) sterile inulin powder was added to 100 g of biofilm that was previously divided in small pieces, the mixture being homogenised and freeze-dried [ 12 ]. The resulting biofilm was finally mortared and stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…During the fermentation process, yeast provides a variety of nutritive elements, such as amino acids, vitamins and pyruvate, to lactic acid bacteria (Fleet 2008). At the same time, the metabolites from lactic acid bacteria provide an energy source for yeast (Pihurov et al 2022). Previous studies have shown that these microbes can not only play an important role in the sensory quality development of dairy products (Perin et al 2017;Moubasher et al 2018;Sahina et al 2022), but also can inhibit the growth of certain bacteria or fungi through the metabolites produced during the fermentation process, thereby contributing to the microbial stability of the final product (Perin et al 2015;Colombo et al 2020;Merchán et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the metabolites from lactic acid bacteria provide an energy source for yeast (Pihurov et al . 2022). Previous studies have shown that these microbes can not only play an important role in the sensory quality development of dairy products (Perin et al .…”
Section: Introductionmentioning
confidence: 99%
“…The last two articles of this series used statistical analysis and mathematical modeling to optimize the fermentation process to obtain new products with improved functional properties. In this frame, Pihurov et al [ 7 ] tested the functionality of a co-culture of SCOBY-based membranes (Kombucha culture known as SCOBY-Symbiotic Culture of Bacteria and Yeasts) and milk kefir grains to produce functional bioactive compounds by fermenting a newly formulated black tea infusion medium supplemented with bovine colostrum and sugar. The chemical composition of the fermented product obtained under the optimized fermentation conditions positively impacted its functional properties in terms of antimicrobial and antioxidant properties.…”
mentioning
confidence: 99%